Josephson inductance as a probe for highly ballistic semiconductor-superconductor weak links - Baumgartner, Christian; Fuchs, Lorenz; Frész, Linus; Reinhardt, Simon; Gronin, Sergei; Gardner, Geoff; Manfra, Professor Michael J; Paradiso, Nicola; Strunk, Christoph (arXiv: Superconductivity, 2020)
We present simultaneous measurements of Josephson inductance and DC transport characteristics of ballistic Josephson junctions based upon an epitaxial Al-InAs heterostructure. The Josephson inductance at finite current bias directly reveals the current-phase relation. The proximity-induced gap, the critical current and the average value of the transparency [τ] are extracted without need for phase bias, demonstrating, e.g., a near-unity value of [τ]=0.94. Our method allows us to probe the devices deeply in the non-dissipative regime, where ordinary transport measurements are featureless. In perpendicular magnetic field the junctions show a nearly perfect Fraunhofer pattern of the critical current, which is insensitive to the value of [τ]. In contrast, the signature of supercurrent interference in the inductance turns out to be extremely sensitive to [τ].